EDUCATION FUNDING AS A DETERMINANT OF THE EDUCATIONAL SYSTEM'S EFFECTIVENESS AND SOCIETAL PERFORMANCE - Sergiy Londar; Oleksandr Bosenko; Lidia Londar; Marcus Pietsch (Фінансово-кредитна діяльність: проблеми теорії та практики)
The article aims to analyze approaches to evaluating secondary education effectiveness across various countries by examining the relationship between public expenditures and students' corresponding learning outcomes, as well as broader societal efficiency indicators. The research explores the correlation between general secondary education funding and international PISA assessment results, alongside the relationship between societal efficiency indicators – such as the Human Development Index (HDI) and GDP at Purchasing Power Parity (PPP) – with educational expenditures and investments in research and development (R&D). The findings demonstrate a non-linear relationship between PISA scores in countries that participated in the 2015, 2018, and 2022 assessments and the cumulative nine-year education funding per 15-year-old schoolchild, expressed in USD at PPP. This relationship is best approximated by an inverted parabola with a peak. Using PISA 2022 as a case study, the educational characteristics of leading countries (Vietnam, Singapore, Macau, Japan) and underperforming countries (Qatar, Panama, Cyprus, the Dominican Republic, and Thailand) were analyzed. These countries' educational outcomes fall outside the standard deviation range. Approaches to evaluating the overall efficiency of education systems were also tested, utilizing widely recognized indicators such as the HDI, GDP per capita at PPP, and the share of public expenditures allocated to R&D. A model was developed to analyze the interrelation between the HDI, R&D expenditures, and per-student educational spending in connection with student performance for a group of countries with high R&D investments. The resulting determination coefficient is R² = 69,7% and confirms the statistical significance of this relationship. The model demonstrates that increased R&D spending has a lesser impact on the HDI compared to educational expenditures on secondary education, adjusted for PISA scores. This finding suggests that, even for developed countries, prioritizing human capital general development through educational investment remains more critical than allocating additional resources to the R&D sector.